PENGARUH PERSONAL SELLING, SALES PROMOTION TERHADAP PENINGKATAN VOLUME PENJUALAN (Studi Empiris Pada CV.Lion Kota Ternate 2013-2017 ) - Ida Hidayanti; Sulfi Abdulhaji (Jurnal Manajemen Sinergi, 2019)
This study aims to test whether Personal Selling, Sales Promotion has an effect on Increasing Sales Volume at Cv. Lion City of Ternate. The population in this study is all sales reports for 2013-2017 on CV. Lion Honda Ternate City. The sampling method uses saturated samples or sampling census where all members of the population are sampled. So that the sample in this study amounted to 60. The technique of collecting data used was by means of documentation observation techniques by collecting lists of increasing sales volumes. The analytical method used is multiple regression analysis with the help of SPSS 23.0 Software. The results of this study found that the Personal Selling variable had an effect on Sales Volume, and the Sales Promotion variable had no effect on Sales Volume.